Varones víctimas de violencia doméstica: un estudio exploratorio acerca de su percepción y aceptación (2010)
A novel fact in the phenomenon of the domestic violence is the men who begin to denounce they are victims of their women, but at the moment exists very little investigation. Our objective was to identify in 100 heterosexual men what attitudes and behaviors perceived like violent in their pair as well as the frequency and modalities whereupon appeared: 50 of them with a relation of engagement and 50 married. VIDOFyP inventory was applied in Mexico's City. Low violence levels were found on both samples, but there was a greater incidence and a greater perception in married men. The modalities with a greater incidence and better perceived by both groups were psychological, social and sexual. A positive correlation between perception and frequency was observed, suggesting that the discrimination of attitudes and violent behaviors is not enough so that they are able to be avoided.